Lordship in four realms : The Lacy family, 1166-1241 - Veach, Colin (Book collections on Project MUSE., 2014)
This title examines the rise and fall of the aristocratic Lacy family in England, Ireland, Wales, and Normandy. As one of the first truly transnational studies of individual medieval aristocrats, it provides a fresh look at lordship and the interplay between aristocracy and crown from 1166 to 1241.